(untitled) (Journal of Applied Oral Science, 2013)
OBJECTIVE: This study aimed to evaluate the effects of heat treatment on the tribochemical silica coating and silane surface conditioning and the bond strength of rebonded alumina monocrystalline brackets. MATERIAL AND METHODS: Sixty alumina monocrystalline brackets were randomly divided according to adhesive base surface treatments (n=20): Gc, no treatment (control); Gt, tribochemical silica coating + silane application; Gh, as per Gt + post-heat treatment (air flux at 100ºC for 60 s). Brackets were bonded to the enamel premolars surface with a light-polymerized resin and stored in distilled water at 37ºC for 100 days. Additionally, half the specimens of each group were thermocycled (6,000 cycles between 5-55ºC) (TC). The specimens were submitted to the shear bond strength (SBS) test using a universal testing machine (1 mm/min). Failure mode was assessed using optical and scanning electron microscopy (SEM), together with the surface roughness (Ra) of the resin cement in the bracket using interference microscopy (IM). 2-way ANOVA and the Tukey test were used to compare the data (p>;0.05). RESULTS: The strategies used to treat the bracket surface had an effect on the SBS results (p=0.0), but thermocycling did not (p=0.6974). Considering the SBS results (MPa), Gh-TC and Gc showed the highest values (27.59±6.4 and 27.18±2.9) and Gt-TC showed the lowest (8.45±6.7). For the Ra parameter, ANOVA revealed that the aging method had an effect (p=0.0157) but the surface treatments did not (p=0.458). For the thermocycled and non-thermocycled groups, Ra (µm) was 0.69±0.16 and 1.12±0.52, respectively. The most frequent failure mode exhibited was mixed failure involving the enamel-resin-bracket interfaces. CONCLUSION: Regardless of the aging method, Gh promoted similar SBS results to Gc, suggesting that rebonded ceramic brackets are a more effective strategy.